Self-motion analysis of extensible continuum manipulators - Kapadia, Apoorva D.; Walker, Ian D. (2013 IEEE International Conference on Robotics and Automation, 2013)
While the field of continuum manipulators has been the subject of increasing attention from the robotics community, knowledge of their inherent capabilities is still limited. Controllers have been proposed that exploit the null-space of redundant continuum manipulators, however studies of the nature of continuum robot null-spaces have not yet been done. In this paper, we first develop a convenient set of extensible, continuum manipulator forward kinematics and resolved-motion rate inverse kinematics. This allows us to analyze the null-space of 2-section, planar, extensible, redundant continuum manipulators to consider the underlying structure of general continuum robot self-motions and discuss their importance to real-world examples and applications.